Humanist Values in Kiai Leadership in Islamic Boarding Schools - Afiful Hair, Moh. (Journal of Islamic Elementary Education, 2023)
Pesantren has long been an Islamic educational institution in Indonesia. Of course, all of this cannot be separated from the Kiai's leadership role in it. Starting from the leadership of the charismatic Kiai, autocratic, democratic, especially humanistic leadership, all of them have an influence on the progress of the pesantren. As with Humanist leadership, with its application in a boarding school. This research uses qualitative research or more precisely mini research, which means to correlate the phenomena found with existing theories. The humanist leadership of a kiai focuses on the nature of humanity or humanity, considering students as real human beings, not as objects, let alone being made as "soldiers" in the Kiai's personal interests.